Evaluasi Kegagalan Dinding Penahan Tanah Pada Lereng Jalan Raya Rembangan Kabupaten Jember - Ayu Dwi Lestari; Paksitya Purnama Putra; Indra Nurtjahjaningtyas (Universitas Islam 45, 2022)
A reinforced concrete type retaining wall was built in 2017 to strengthen the slope stability of Rembangan highway, Jember Regency, Indonesia. However, in 2018 the building was damage. Until now, the cause of the failure of the retaining wall is still unknown. This study aims to evaluate the causes of the failure of retaining walls and the stability of retaining walls on the slopes of the Rembangan highway, Jember Regency. The research methodology begins with primary and secondary data collection before processing the data using conventional methods and auxiliary software. After data processing, data analysis was carried out to find conclusions about the cause of the failure of the retaining wall. Result analysis showed that the retaining walls have a low level of safety factor for rolling stability, shear stability, and bearing capacity stability. In addition, the factor of safety for the bearing capacity of the group pile foundation as a reinforcement of retaining walls also shows a smaller value than that charged. In addition, the group pile foundation can suffer a total settlement of 1.28 m.